CCAFS-Climate Data Portal - International Center for Tropical Agriculture; CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
The datasets contained in this website are part of the International Centre for Tropical Agriculture (CIAT) climate change downscaled data, developed in the Decision and Policy Analysis (DAPA) program. The data have been originally downloaded from the IPCC data portal and re-processed using an spline interpolation algorithm of the anomalies and the current distribution of climates from the WorldClim database developed by Hijmans et al. (2005). All GCMs presented here come from the fourth and third IPCC Assessment Reports, but in further updates of the webpage, only models from the 4AR will be kept.